2000
DOI: 10.1177/154193120004400213
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Model for Determining the Impact of Password Authentication Practices on Information Security

Abstract: This research focuses on the development of a model for evaluating the human impact that password authentication issues are having on the security of information systems. Through observational analysis, organizational policy, and retrospective analysis, researchers created a model for predicting the vulnerability that a particular set of conditions will have on the likelihood of error in an information system. The methodology for the experiment and analysis of the results are presented. The findings indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 3 publications
3
37
1
Order By: Relevance
“…An example of this category would be an authorized user of a system who is unable to access a system due to forgetting his or her password. Given the above definitions, a human-error security incident is defined as any human-error-related event that compromises information's confidentiality, integrity, or accessibility (Carstens et al, 2004).…”
Section: Information Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…An example of this category would be an authorized user of a system who is unable to access a system due to forgetting his or her password. Given the above definitions, a human-error security incident is defined as any human-error-related event that compromises information's confidentiality, integrity, or accessibility (Carstens et al, 2004).…”
Section: Information Securitymentioning
confidence: 99%
“…Preliminary research conducted in the area of the human impact on information security indicated that 37% of survey participants never change their work and/or school passwords and that 69% of survey participants never change their personal passwords (Carstens et al, 2004). The same research indicated that when prompted to replace a current password, 43% of survey participants changed their work and/or school passwords back to a password they had used in the past; 33% of survey participants indicated changing their personal passwords back to an old password as well.…”
Section: Human Error In Information Securitymentioning
confidence: 99%
“…(Dourish, dl Flor & Joseph 2003) (Carstens et al 2004) (Adams, Sasse & Lunt 1997) (Werlinger et al, 2009) (Veiga & Eloff 2009) (Kraemer and Carayon, 2005) (Kraemer et al, 2009) (Knapp, Marshall & Rainer 2006) (Pattinson and Anderson, 2007) (Tsohou et al, 2006). The research most closely related to the topic is described below.…”
Section: Human and Organizational Factors Causing Vulnerabilitiesmentioning
confidence: 99%
“…With the introduction of biometric devices into various sectors of economy, there should be more education on this technology (Moody, 2004). More education and simple tips on how users should choose and manage passwords may avoid the problem of weak passwords, human errors, and exposure to intruders (Carstens, McCauley-Bell, & DeMara, 2004). The course has to be based on the model of teaching students a combination of theoretical concepts and hands on practice of security.…”
Section: Achieving Better Awareness Education In Information Securitymentioning
confidence: 99%